Russians, Belarusians and Borderland Poles in a historical anecdote, or what people laughed at over 100 years ago - Jurkowski, Roman (Laughter, humour, satire, 2024)
The article presents several anecdotes from the late 19th and early 20th centuries in the Taken Territories of the First Polish Republic. They talk about Russians, Belarusians and Poles. In addition to the dose of humor and joke that is indispensable in every anecdote, they differ from each other in their attitude to the nation they refer to. In the anecdotes referring to the Russians, one can see criticism, sharper satire, even malice – they were, after all, the invaders. Belarusians have been part of the borderland society for a long time, so they are treated with understanding due to the youngest member of the family. And the Poles were different. From freaks through patriots to jokers. The presented anecdotes are part of the history of the Taken Lands and the nations living there.